DenseNet weed recognition model combining local variance preprocessing and attention mechanism - Mu, Ye; Ni, Ruiwen; Fu, Lili; Luo, Tianye; Feng, Ruilong; Li, Ji; Pan, Haohong; Wang, Yingkai; Sun, Yu; Gong, He; Guo, Ying; Hu, Tianli; et al. (Frontiers in Plant Science, 2023)
Introduction The purpose of this paper is to effectively and accurately identify weed species in crop fields in complex environments. There are many kinds of weeds in the detection area, which are densely distributed. Methods The paper proposes the use of local variance pre-processing method for background segmentation and data enhancement, which effectively removes the complex background and redundant information from the data, and prevents the experiment from overfitting, which can improve the accuracy rate significantly. Then, based on the optimization improvement of DenseNet network, Efficient Channel Attention (ECA) mechanism is introduced after the convolutional layer to increase the weight of important features, strengthen the weed features and suppress the background features. Results Using the processed images to train the model, the accuracy rate reaches 97.98%, which is a great improvement, and the comprehensive performance is higher than that of DenseNet, VGGNet-16, VGGNet-19, ResNet-50, DANet, DNANet, and U-Net models. Discussion The experimental data show that the model and method we designed are well suited to solve the problem of accurate identification of crop and weed species in complex environments, laying a solid technical foundation for the development of intelligent weeding robots.